Comportamento temporal da evapotranspiração de referência em municípios de são paulo e províncias de cuba - Conde, Esteban Choque [UNESP]; de Brito, Ramilos Rodrigues [UNESP]; Montenegro, Ranses José Vázquez; Román, Rodrigo Máximo Sánchez [UNESP] (My University, 2016)
The importance of determining and modelling the temporal behavior of Reference Evapotranspiration (ETo) lies in the need to generate a margin of confidence in programming and assess the availability of water for irrigation, considering future demands to diminish the water deficit for agricultural crops. The study focuses on the estimation of ETo by Penman- Monteith FAO-56 equation, and modeling the tendency and temporal behavior, by using semivariogram analysis and kriging as geo-statistical methods. The areas of study were Güira de Melena, Bauta and Batabanó in Cuba, and Franca, Piracicaba and São Paulo in Brazil. The results of the ETo showed several scenarios, larger amplitudes during the summer solstice and smaller in the winter solstice.
Temporal behavior of reference evapotranspiration in the state of são paulo and provinces of Cuba
Keywords: Geostatistic; Kriging; Reference evapotranspiration